2013
DOI: 10.1021/nl304069n
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering with Ag Nanoparticles Optically Trapped by a Photonic Crystal Cavity

Abstract: We demonstrate a reusable and reconfigurable surface enhanced Raman scattering (SERS) platform by optically trapping Ag nanoparticles with a photonic crystal cavity integrated with a microfluidic chip. High-performance SERS is performed in a very reproducible manner, owing to the fact that Ag aggregates are produced by optical trapping in a controllable process that is monitored in real-time by the cavity resonance shift that occurs with the trapping of each additional nanoparticle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 30 publications
3
83
0
Order By: Relevance
“…Sophisticated slotted waveguides [141,[151][152][153] as well as nanobeam cavities [140,146,150,[154][155][156][157][158][159][160] have also been implemented for analyte-specific stoichiometric studies and biomolecule micromanipulation. Extreme, sub-attomolar detection of a streptavidin protein was reported for nanoslot PhC nanolasers [139,[161][162][163][164][165][166][167][168], while novel PhC nanocavities combined with plasmonic nanostructures have emerged as hybrid photonic-plasmonic biosensors [169][170][171][172][173][174][175][176][177][178][179]. Unusually sensitive biodetection down to the single-molecule level with nanostructured materials comprising selfassembled silver nanoparticles on PhC diatom biosilica [180,181] and a gold antenna-in-a-nanocavity [182] substantiates the fast and steady advancement of hybrid photonic-plasmonic instrumentation utilising PhCs.…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
“…Sophisticated slotted waveguides [141,[151][152][153] as well as nanobeam cavities [140,146,150,[154][155][156][157][158][159][160] have also been implemented for analyte-specific stoichiometric studies and biomolecule micromanipulation. Extreme, sub-attomolar detection of a streptavidin protein was reported for nanoslot PhC nanolasers [139,[161][162][163][164][165][166][167][168], while novel PhC nanocavities combined with plasmonic nanostructures have emerged as hybrid photonic-plasmonic biosensors [169][170][171][172][173][174][175][176][177][178][179]. Unusually sensitive biodetection down to the single-molecule level with nanostructured materials comprising selfassembled silver nanoparticles on PhC diatom biosilica [180,181] and a gold antenna-in-a-nanocavity [182] substantiates the fast and steady advancement of hybrid photonic-plasmonic instrumentation utilising PhCs.…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
“…It has been shown that the mechanical vibrations can be sustained in a liquid core optical ring resonator, a liquid filled capillary that enables the determination of the mechanical properties of a sample, such as viscosity, which can change for example by the amount of dissolved glucose [18]. First steps towards adding Raman spectroscopy to microcavity biosensing were taken recently: trapped particles on a ring resonator were utilized to enhance and collect the Raman signal of a model analyte [63]. Furthermore, the trapping of nanoparticles can find utility in size spectroscopy of particles, and enhancing measurement signals [64][65][66][67].…”
Section: Biodetection Mechanismsmentioning
confidence: 99%
“…Dark field microscopy is a useful tool for NP sensing, but with contrast that decreases as 1/r 6 of the NP [9,34], and is not able to discriminate scattering centers that are not nanoparticles [8]. Contrast for sensing NPs can be enhanced when their absorption spectra can be coupled to dielectric high quality-factor (Q-factor) resonators [35][36][37] or moderate Q-factor nanostructured surfaces [38].…”
Section: Introductionmentioning
confidence: 99%